The Influence of Culture on Attitudes Towards Humorous Advertising - Wang, Yi; Lu, Su; Liu, Jia; Tan, Jiahui; Zhang, Juyuan (Frontiers in Psychology, 2019)
Humor has been widely used in advertising in recent decades. Various studies found that humor could significantly improve advertising performance. However, most of these studies were conducted in a Eastern context and did not consider cultural factors. In a cross-cultural research framework, the current study explored the effects of advertisement characteristics (i.e., brand nationality and humor tactics) on Chinese and United States audiences’ attitudes toward humorous advertisements. Results showed that the attitudinal differences between Chinese audiences and United States audiences was not significant at the aggregate level. Instead, the differences lie in an audience’s responsiveness to characteristics of the ads. Specifically, while United States audiences showed a strong preference for ads featuring Chinese brands compared to those of United States brands, Chinese audiences did not differentiate them. United States audiences preferred ads using self-enhancing tactics to those using affiliative tactics, whereas, again Chinese audiences did not differentiate. We also explored whether individual differences in cultural values could account for the effect of audience nationality. Results suggest that differences embedded in culture groups, as indicated by audience nationality, could not be explained or substituted by individual variance in humor tolerance and uncertainty avoidance. Limitations and future directions were discussed.